Analisis Varians Atas Perhitungan Biaya Standar Sebagai Alat Pengendalian Biaya Produksi Pada Usaha Paving Block PT. Jaya Mandiri - Yeni Elfiza Abbas; Derhen Damanik (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Based on the results of the raw material cost variance analysis, it shows that there is a difference (Favorable), which consists of a raw material price variance and a raw material quantity variance of Rp. 7,679,750. The results of the analysis of variance in labor costs show that there is a difference (Favorable) between standard labor costs and actual labor costs of Rp. 1,901,900, - And finally the analysis of the variance of factory overhead costs also shows a difference (Favorable) of Rp. 215,631.4 which consists of controlled differences and volume differences. As for the achievement of the difference (Favorable) for production costs because the management in the implementation of production as well as controlling raw material costs, labor costs and factory overhead costs has carried out the implementation of standard production cost controls that are effective, correct and appropriate and takes into account historical costs when determining standard cost .